Microscopy-based techniques: A reliable method for detecting Blastocystis sp. Infection - Noradilah S.A.; Moktar N.; Anuar T.S.; Lee I.L.; Salleh F.M.; Manap S.N.A.A.; Mohtar N.S.H.M.; Azrul S.M.; Abdullah W.O.; Nordin A.; Abdullah S.R. (Polish Forest Society, 2024)
Indexed by SCOPUS